2023
DOI: 10.1007/s00535-023-02037-z
|View full text |Cite
|
Sign up to set email alerts
|

Current status and issues in genomic analysis using EUS-FNA/FNB specimens in hepatobiliary–pancreatic cancers

Yoshinori Ozono,
Hiroshi Kawakami,
Naomi Uchiyama
et al.

Abstract: Comprehensive genomic profiling based on next-generation sequencing has recently been used to provide precision medicine for various advanced cancers. Endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) and EUS-guided fine-needle biopsy (EUS-FNB) play essential roles in the diagnosis of abdominal masses, mainly pancreatic cancers. In recent years, CGP analysis using EUS-FNA/FNB specimens for hepatobiliary–pancreatic cancers has increased; however, the success rate of CGP analysis is not clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…However, recent research supports the feasibility of this approach. Choi et al performed EUS-guided tissue acquisition using core needles for solid liver cancers in the left lobe [ 31 ]. In this study, 12 patients had primary liver cancer, including four cases of hepatocellular carcinoma and seven of intrahepatic cholangiocarcinoma, while 16 had metastatic liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research supports the feasibility of this approach. Choi et al performed EUS-guided tissue acquisition using core needles for solid liver cancers in the left lobe [ 31 ]. In this study, 12 patients had primary liver cancer, including four cases of hepatocellular carcinoma and seven of intrahepatic cholangiocarcinoma, while 16 had metastatic liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EUS‐FNB is superior to EUS‐FNA in providing adequate samples for CGP testing. 15 , 25 , 26 , 27 Although the technical excellence of 19G‐FNB has been demonstrated in clinical practice, its sampling adequacy remains limited. Hence, further efforts are required to improve the sampling adequacy for CGP tests.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gallbladder carcinoma (GBC) is associated with pathogenic EGFR, ERBB2/3, PTEN, ARID2, MLL2/3, TERT, TP53, BRCA1/2, and PIK3CA variants. 5 FGFR2 variants have been studied extensively in the context of intrahepatic CCA, and therapies targeting such genetic changes, including pemigatinib and futibatinib, demonstrated promising response rates of 35.5% and 42%, respectively, when used as second-line treatments. 6 , 7 …”
mentioning
confidence: 99%
“…However, the tissue quantity adequacy rates remained undocumented in these reports. 5 These studies were predominantly limited by patient selection, with most enrolled patients suffering from intrahepatic CCA or GBC and very few cases representing ductal infiltration and extrahepatic CCA. Notably, a study evaluating EUS-FNA efficacy in pancreatic cancer reported CGP adequacy rates of 72.5%, 53.5%, and 33.3% for 19-G-FNB, 22-G-FNB, and 22-G-FNA, respectively.…”
mentioning
confidence: 99%